Purification, characterization and antiglycation activity of a novel polysaccharide from black currant. (15th May 2016) - Xu, Yaqin; Liu, Gaijie; Yu, Zeyuan; Song, Xiumei; Li, Xingguo; Yang, Yu; Wang, Libo; Liu, Lu; Dai, Jing
Highlights: BCP-1 was purified by macroporous resin D4006, anion-exchange Q-Sepharose FF and Sephadex G-100 column chromatography. BCP-1 was characterized by HPLC, GC, FT-IR, NMR, SEM and Congo red test. BCP-1 exhibited strong antiglycation activity. Abstract: A novel polysaccharide fraction (BCP-1) was extracted from the black currant fruit by ultrasound-assisted compound enzyme and purified by chromatography on macroporous resin D4006, anion-exchange Q-Sepharose FF and Sephadex G-100 columns. BCP-1 consisted of galacturonic acid, xylose, mannose, glucose and galactose in a ratio of 1.00:3.14:1.83:17.90:1.98 and its molecular weight was 14, 050 Da. The preliminary structure features of BCP-1 were investigated by FT-IR and NMR. SEM and Congo red test showed that BCP-1 had honeycomb-like structure, but no triple helix structure. BCP-1 exhibited significant inhibitory abilities on protein glycation. Especially, BCP-1 showed obvious inhibitory effects on the formation of dicarbonyl compounds and AGEs (% inhibition of 66.95 ± 0.33% and 67.15 ± 0.40% respectively), but weaker inhibition Amadori compound production (max. 37.15 ± 0.36% inhibition). This suggested that the inhibitory action of BCP-1 on protein glycation was more effective on the later phases of dicarbonyl compounds and AGEs formation.